2011
DOI: 10.4025/actascianimsci.v33i1.10787
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho, digestibilidade, composição corporal e morfologia intestinal de pintos de corte recebendo dietas contendo levedura de cana-de-açúcar

Abstract: Objetivou-se avaliar o desempenho, a digestibilidade das dietas, a retenção corporal de nutrientes e o desenvolvimento da mucosa intestinal de pintos de corte de 1 a 8 dias de idade, alimentados com dietas contendo níveis crescentes de levedura de cana-de-açúcar. Utilizou-se 300 pintos de corte, com um dia de idade, distribuídos em delineamento inteiramente casualizado, composto de cinco tratamentos e seis repetições de 10 aves. Os tratamentos consistiram de níveis crescentes de 0; 1,25; 2,5; 3,75 e 5,0% de in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…Similar results were obtained by Yang et al (2007) and Lopes et al (2011), who did not observe effects of MOS or whole yeast cell on body weight and weight gain of 21-day-old and seven-dayold broilers, respectively.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were obtained by Yang et al (2007) and Lopes et al (2011), who did not observe effects of MOS or whole yeast cell on body weight and weight gain of 21-day-old and seven-dayold broilers, respectively.…”
Section: Resultssupporting
confidence: 75%
“…Additionally, the extract of yeast has nucleotides and inositol, which help the cell synthesis process in the villus by increasing its size. Lopes et al (2011) worked with whole yeast cell and observed greater villus heights in the segments of the small intestine on the 7th day of age, without any effects on performance.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Nunes et al (2009) os resultados referente à morfologia intestinal no duodeno não evidenciaram efeito positivo dos aditivos alternativos (prebiótico e probiótico) em relação ao grupo controle, sendo que a altura do vilo e a profundidade da cripta encontrada são superiores a do presente trabalho. Lopes et al (2011), não observaram efeito da inclusão de levedura sob nível de inclusão de 0; 1,25; 2,5; 3,75 e 5,0% em nenhum dos parâmetros avaliados em pintos de oito dias. A altura do vilo e a profundidade da cripta encontradas por Nunes et al (2009) e Lopes et al (2011 não se equipararam com os resultados obtidos, visto que as análises por eles realizadas foram experimentais e não a campo, e isso pode ter influenciado nos resultados dos experimentos.…”
Section: Resultsunclassified
“…Sugarcane yeast and protein feed have been studied by researchers in the search for a substitute to soybean meal in poultry feed (FREITAS et al, 2013), as this is a product that is widely available on the market through its link to the processes of ethanol production (LOPES et al, 2011). The interest in this ingredient concerning animal feed is founded principally on its high rate of protein, at around 37.20% of crude protein, however, only 21.58% of this is digestible (ROSTAGNO et al, 2011).…”
Section: Introductionmentioning
confidence: 99%